Bilateral deep brain stimulation of the subthalamic nucleus effectively relieves dystonia secondary to Fahr's disease: a case report. (1st August 2013) - Ma, Yu; Ge, Ming; Meng, Fangang; Zhang, Kai; Zhang, Jianguo
Abstract : Fahr's disease (FD) is a rare movement disorder characterized by bilateral intracranial calcifications that is refractory to most treatments. We present the case of a 26-year-old male with FD who was unable to walk independently and could not eat solid food because of poor swallowing capability and severe cervical dystonia. Injections of botulin toxin into the neck muscles, as well as biperiden, tiapride, amantadine, L-dopa and clonazepam were ineffective. Deep brain stimulation (DBS) was performed with two permanent electrodes containing four contact sites implanted bilaterally into the subthalamic nucleus (STN). The antidystonic effect was evident immediately after STN stimulation, and it was sustained during a 24-month follow-up period. There was a marked reduction of cervical dystonia, and he could eat solid food and was able to walk independently. This case demonstrates that DBS of the STN can be effective for the treatment of dystonia associated with FD.